TLR3 impairment in human newborns. Issue 5 (1st November 2013) - Slavica, Lucija; Nordström, Inger; Karlsson, Merja Nurkkala; Valadi, Hadi; Kacerovsky, Marian; Jacobsson, Bo; Eriksson, Kristina
Abstract : Absence of TLR3 mRNA and protein expression in cord blood NK cells and its consequent functional implication. Abstract : Newborns are highly susceptible to viral infections. We hypothesized that this susceptibility could be due to a dysregulated expression of innate virus‐sensing receptors, i.e., TLR3, TLR7, TLR8, and TLR9 and the cytosolic receptors retinoic acid‐inducible gene I, melanoma differentiation‐associated protein 5, protein kinase R, and IFN‐γ‐inducible protein 16. Cord blood mononuclear cells (CBMCs) expressed mRNA for all these receptors except for TLR3. In peripheral blood mononuclear cells (PBMCs), TLR3 mRNA was preferentially expressed in cytotoxic cells, particularly CD56 dim NK cells. Cord NK cells in contrast showed low TLR3 mRNA expression and lacked TLR3 protein expression. Cord NK cells did not produce IFN‐γ in response to polyinosinic‐polycytidylic acid [poly(I:C)], whereas strong IFN‐γ production was observed in poly(I:C)‐stimulated adult NK cells. Cord NK cells had poor cytotoxic function that was only marginally enhanced by exposure to the TLR3 ligand poly(I:C). Opposite to NK cells from adults, their cytotoxicity was not improved by herpes simplex virus (HSV) exposure and they were unable to kill HSV‐infected cells. There were no differences in the TLR3 mRNA levels among men, women, and pregnant women, implying that TLR3 is not under sex hormone control. However, decidual NK cells expressed low levels of TLR3 mRNA, which was attributed to their CD56 bright phenotype. Our data show that cord blood NK cells have deficient TLR3 expression associated with an inability to respond to poly(I:C) and HSV activation and to kill HSV‐infected cells. This might explain why newborns are particularly sensitive to neonatal HSV infections.